An algebra problem by Aaryan Maheshwari

Algebra Level 2

If a + b + c = 0 a+b+c=0 , where a a , b b and c c are non-zero real numbers, then calculate the value of

( a 2 b c ) 2 ( b 2 c a ) ( c 2 a b ) \large (a^2-bc)^2-(b^2-ca)(c^2-ab)


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Aaryan Maheshwari
Aug 23, 2017

Relevant wiki: Algebraic Identities

We have been given: ( a 2 b c ) 2 ( b 2 c a ) ( c 2 a b ) . \text{We have been given:}\space (a^2-bc)^2-(b^2-ca)(c^2-ab).

Simplifying the above expression, we get: \text{Simplifying the above expression, we get:}

a 4 + a b 3 + a c 3 3 a 2 b c = a ( a 3 + b 3 + c 3 3 a b c ) a^4+ab^3+ac^3-3a^2bc\space =\space a(a^3+b^3+c^3-3abc)

Now, we will prove that if a + b + c = 0 , we have a 3 + b 3 + c 3 = 3 a b c . \text{Now, we will prove that if}\space a+b+c=0, \text{we have}\space a^3+b^3+c^3=3abc.

Since we know that a 3 + b 3 + c 3 3 a b c = ( a + b + c ) ( a 2 + b 2 + c 2 a b b c c a ) , we have: \text{Since we know that}\space a^3+b^3+c^3-3abc=(a+b+c)(a^2+b^2+c^2-ab-bc-ca), \text{we have:}

a 3 + b 3 + c 3 3 a b c = 0 × ( a 2 + b 2 + c 2 a b b c c a ) = 0. Thus, a^3+b^3+c^3-3abc= 0\times(a^2+b^2+c^2-ab-bc-ca)=0. \text{Thus,}

a ( a 3 + b 3 + c 3 3 a b c ) = a × 0 = 0 . \therefore\space a(a^3+b^3+c^3-3abc)=a\times0=\boxed{0}.

Nice solution! Some typos in the third line :)

Sathvik Acharya - 3 years, 9 months ago

Fixed.. thanks for the compliment😁

Aaryan Maheshwari - 3 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...